Dystrophic pulpal calcification and crown darkening as sequelae of dental trauma: Report of two cases - Tiago Martins Feijó Miguelis; Josué Martos; Melissa Feres Damian; Giovane Hisse Gomes; Cristina Braga Xavier; Juan Pablo Aitken Saavedra (Wolters Kluwer Medknow Publications, 2021)
Dystrophic calcification of pulp tissue is a phenomenon that occurs more frequently in teeth with a history of concussion and luxation or even in avulsed and replanted teeth. The objective of this report is to describe the posttraumatic dystrophic calcification of the pulp, approaching a conservative treatment illustrated with clinical cases. The patients had intense yellowing of the dental crown of anterior teeth, and in the pulp sensitivity tests, a negative response was obtained on traumatized teeth. In both the cases, the periapical radiographic examination showed canal calcification. The clinical and radiographic findings revealed a diagnosis of pulp canal obliteration of traumatized teeth resulting from a sequel of dental trauma. The in-office dental bleaching by using hydrogen peroxide at 35% in two patients was the treatment option performed. The clinical responses of in-office dental bleaching in the presented cases of dystrophic calcification of the pulp were effective. It was possible to conclude that dental bleaching with hydrogen peroxide in two clinical sessions presented satisfactory and harmonic results.